Practical ultrasound an illustrated guide - Alty, Jane; Hoey, Edward (CRC Press, 2013)
In the hands of a skilled operator, ultrasound scanning is a simple and easy procedure. However, reaching that level of proficiency can be a long and tedious process. Commended by the British Medical Association, Practical Ultrasound, Second Edition focuses on the scans regularly encountered in a busy ultrasound department and provides everything practitioners need to know to become competent and skilled in scanning.